PENGEMBANGAN MEDIA PEMBELAJARAN KIMIA RAMAH BUDAYA: DAKONIC BERBASIS PERMAINAN DAKON - Inka Piola; Permatasari, ⁠Afita; Kautsar Althaf D.I.H, ⁠Salsabila; Puji Astuti, ⁠Andari (UIR Press, 2025)
This study developed a culturally responsive chemistry learning media based on the traditional game dakon, named DAKONIC (Dakon Periodic Chemistry), for teaching the Periodic Table of Elements. The research employed a Research and Development (R&D) method using the ADDIE model, involving 36 tenth-grade students at SMA Negeri 15 Semarang. Validation by material experts, media experts, and teachers indicated that DAKONIC was highly feasible with a 90% validity score. Practicality testing from teachers and students achieved 87% (practical category). Effectiveness testing using a paired sample t-test showed a significance value of 0.000 (< 0.05), confirming that DAKONIC effectively improved students’ understanding of the periodic table. The media was designed from recycled wood (90 × 30 cm) with 18 holes representing groups and periods, 2 large scoring holes, 118 element replicas, and 56 educational challenge cards. It is portable and equipped with a teaching module to support the Teams Games Tournament (TGT) cooperative learning model. Findings demonstrate that DAKONIC is feasible, practical, and effective, successfully integrating local cultural wisdom with modern chemistry learning.